Collective preventive diplomacy : a study in international conflict management - Steiner, Barry H. (Barry Howard), 1942- (SUNY series in global politics., 2004)
"This study focuses on why and how powerful nations have acted together to dampen or forestall the expansion of small state conflicts while limiting potential risks to themselves. Employing a case-study method, Barry H. Steiner distinguishes between two types of collective preventive diplomacy, the insulationist and the interventionist. In the former, powerful nations are motivated to contain small power conflict in order to preserve their relations with other powerful nations. In the latter, they act to settle conflict between the small power antagonists themselves."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved